QUALITY IMPROVEMENT MANAGEMENT LEARNING AT IT JUNIOR HIGH SCHOOL (SMP IT) AL KAFFAH BINJAI - Syafaruddin Syafaruddin; Mesiono Mesiono; Asnawati Asnawati (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study is to analyze the management of improving the quality of learning at SMP IT Al Kaffah Binjai, from the aspects of planning, organizing, implementing and monitoring. This study uses a qualitative approach with descriptive analytical study method. Data collection was done through interviews, observation and documentation techniques. Data analysis was carried out through data reduction, data presentation, and data verification. The results of this study indicate that efforts to improve the quality of learning at SMP IT Al Kaffah are managed well and effectively. This is viewed from (1) planning, including the formation of a curriculum development team, managing learning activities according to the national education calendar, ensuring teachers create learning programs, planning for student recruitment preparations (new students or transfer students), school orientation and additional programs, and preparation learning planning documents; (2) organizing, including a structured delegation of school organization, starting from the founder delegating it to the foundation, the foundation delegating it to the principal, as well as the principal who is assisted by representatives, teachers and education staff; (3) implementation, including the process of interaction between teachers and students as well as learning facilities; and (4) supervision, including internal supervision (principal) and external supervision (supervisor from the Binjai City Education Office), which oversees the academic and managerial aspects of the school.